The steamboat phoenix and the archaeology of early steam navigation in North America - Schwarz, George R, author.
1 online resource (236 pages)
Keywords: The Steamboat Phoenix and the Archaeologyof Early Steam Navigation in North Americaoffers an in-depth exploration of the archaeological and cultural aspects of early American steamboat development. It also tells the story of Phoenix, the second steamer to operate on Lake Champlain and the world’s earliest archaeologically studied steamboat wreck. In doing so, this book provides a unique insight into early perceptions of steam navigation, including both the wonder and fear elicited by the comfort and efficiency they promised and the hazards with which they came to be associated.